UTILIZING MICROSOFT MATHEMATICS IN TEACHING AND LEARNING CALCULUS - Oktaviyanthi, Rina; Supriani, Yani (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2015)
The experimental design was conducted to investigate the use of Microsoft Mathematics, free software made by Microsoft Corporation, in teaching and learning Calculus. This paper reports results from experimental study details on implementation of Microsoft Mathematics in Calculus, studentsÃ¢â‚¬â„¢ achievement and the effects of the use of Microsoft Mathematics on studentsÃ¢â‚¬â„¢ attitudes in relation to such experience. Two classes of the students from the first year student in Universitas Serang Raya were participated in the study. This study found that students who taught by using Microsoft Mathematics had higher achievement and has a positive effect on studentsÃ¢â‚¬â„¢ confidence of mathematics.Keywords: Calculus, Educational Technology, Mathematics Education, Microsoft Mathematics, Technology ApplicationÃ‚Â DOI: dx.doi.org/10.22342/jme.61.63